Republic of Kazakhstan : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2012 Article IV Consultation reports that fiscal and monetary policies have adapted to the economic recovery in the Republic of Kazakhstan. The authorities have appropriately responded to the upswing in the cycle by gradually tightening fiscal policy and sterilizing excess bank liquidity. Directors have commended the authorities' policies that, together with high commodity prices, yielded a strong economic recovery. Directors have also appreciated the preparation of plans to deal with a possible protracted global slowdown and a decline in oil prices.